A three-phase coil coupling wireless power transfer pad for electric vehicles battery charging systems - Mahesh Aganti; Bharatiraja Chokkalingam; Sanjeevikumar Padmanaban; Sheldon S. Williamson (Results in Engineering)
Resonant Inductive Power Transfer (RIPT) is pivotal in advanced Electric Vehicle (EV) charging systems, offering safety, reliability, and automation ease. The magnetic pad design within RIPT-based Wireless Charging Systems (WCS) significantly influences power transfer efficiency. Three-phase magnetic couplers outshine their single-phase counterparts in energy transfer capacity, offering benefits like rotating magnetic flux and reduced ferrite mass. This article analyzes a three-phase magnetic coupler design featuring a circular geometry, characterized by enhanced angular misalignment tolerance, ferrite-friendly structure, and ease of design. Named the ''Three Half Circular Coil'' (3HCC) pad, it comprises three half-circular coils arranged in a circular pattern. The performance of this design is rigorously analyzed using MATLAB and Ansys Finite Element for a 7.7 kW system. The proposed model is benchmarked against a tripolar coil, a three-phase rectangular coil, and a conventional single-phase circular coil. 7.7 kW experimental models are designed and analyzed to investigate cross-coupling effects as the coil moves away from the origin. This article underscores the critical role of RIPT in EV charging systems, highlights the advantages of three-phase magnetic couplers over single-phase, and showcases the effectiveness of the proposed 3HCC design.